Perceived Gesture Dynamics in Nonverbal Expression of Emotion. (June 2013) - Dael, Nele; Goudbeek, Martijn; Scherer, K R
Recent judgment studies have shown that people are able to fairly correctly attribute emotional states to others' bodily expressions. It is, however, not clear which movement qualities are salient, and how this applies to emotional gesture during speech-based interaction. In this study we investigated how the expression of emotions that vary on three major emotion dimensions—that is, arousal, valence, and potency—affects the perception of dynamic arm gestures. Ten professional actors enacted 12 emotions in a scenario-based social interaction setting. Participants (N = 43) rated all emotional expressions with muted sound and blurred faces on six spatiotemporal characteristics of gestural arm movement that were found to be related to emotion in previous research (amount of movement, movement speed, force, fluency, size, and height/vertical position). Arousal and potency were found to be strong determinants of the perception of gestural dynamics, whereas the differences between positive or negative emotions were less pronounced. These results confirm the importance of arm movement in communicating major emotion dimensions and show that gesture forms an integrated part of multimodal nonverbal emotion communication.